Solve for s s/-4=6

Math
s-4=6
Multiply both sides of the equation by -4.
-4⋅s-4=-4⋅6
Simplify both sides of the equation.
Tap for more steps…
Simplify -4⋅s-4.
Tap for more steps…
Cancel the common factor of 4.
Tap for more steps…
Factor 4 out of -4.
4(-1)⋅s-4=-4⋅6
Factor 4 out of -4.
4⋅-1⋅s4⋅-1=-4⋅6
Cancel the common factor.
4⋅-1⋅s4⋅-1=-4⋅6
Rewrite the expression.
-1⋅s-1=-4⋅6
-1⋅s-1=-4⋅6
Simplify the expression.
Tap for more steps…
Move the negative one from the denominator of s-1.
-1⋅(-1⋅s)=-4⋅6
Rewrite -1⋅s as -s.
-1⋅(-s)=-4⋅6
-1⋅(-s)=-4⋅6
Multiply -1(-s).
Tap for more steps…
Multiply -1 by -1.
1s=-4⋅6
Multiply s by 1.
s=-4⋅6
s=-4⋅6
s=-4⋅6
Multiply -4 by 6.
s=-24
s=-24
Solve for s s/-4=6

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top